Mitigating Long-term Unemployment in Europe - Suphaphiphat, Nujin (IMF Working Papers; Working Paper ;, 2020)
While unemployment rates in Europe declined after the global financial crisis until 2018/19, the incidence of long-term unemployment, the share of people who have been unemployed for more than one year to the total unemployed, remained high. Moreover, the COVID-19 pandemic could aggravate the long-term unemployment. This paper explores factors associated with long-term unemployment in European countries, using panel of 25 European countries over the period 2000-18. We find that skill mismatches, labor market matching efficiency, and labor market policies are associated with the incidence of long-term unemployment. Among different types of active labor market policies, training and start-up incentives are found to be effective in reducing long-term unemployment.